ANTI-LEISHMANIAL ACTIVITY INVESTIGATION OF SOME NEW QUINAZOLINONE DERIVATIVES - FEROCHE, ALEMU TADESSE; AWOKE, DAGMAWIT; HAILU, ASRAT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
In this study, some new 3-aryl, 2-substituted quinazoline-4 (3H) - one derivatives were synthesized using a three-step synthetic route. They were obtained in a good yield (59.5-85%) by applying different chemical reaction like cyclization and condensation reaction. The chemical structure of the final compounds was also verified by spectroscopic methods (IR, 1HNMR) and elemental microanalysis. The synthesized compounds (IVa, IVb, IVc, IVd, IVe and IVf) were screened for their in vitro anti-leishmanial activity against L. aethiopica isolate (CL/039/09). All tested compounds (IVa (0.03766 µg/ml), IVb (0.00538 µg/ml, IVc (0.00412 µg/ml, IVd (0.00110 µg/ml), IVe (0.03017 µg/ml) and IVf (0.03894 µg/ml)) showed excellent potency that is much better than the standard drug, amphotericin B (IC50 = 0.04359 ug/ml). The results of acute toxicity indicated that all test compounds (IVa, IVb, IVc, IVd, IVe and IVf) proved to be non-toxic and well tolerated by the experimental animals up to 300 mg/kg in oral and 140 mg/kg in parental studies.